Strategi Kepala Sekolah Dalam Peningkatan Mutu Akademik Dan Non Akademik Peserta Didik - Fitriana, Riska Nur; Handayaningrum, Warih; Roesminingsih, Maria Veronika (Lembaga Penelitian dan Pendidikan Mandala, 2021)
In its management, schools need quality assurance as a benchmark for assessing the success or failure of educational institutions. One of the most important aspects that affect the quality of education is leadership and quality management. The research objectives are: (1) to describe how the principal's strategy in improving the academic quality of students at SMAN 2 Sidoarjo (2) to describe how the principal's strategy is to improve the non-academic quality of students at SMAN 2 Sidoarjo. This study uses a qualitative descriptive. Collecting data using the method of observation, interviews and documentation. The results of this study are: (1) the principal's strategy in improving the academic quality of students at SMAN 2 Sidoarjo is through the PPDB process carried out in 4 stages, supervising the learning process in order to know the achievements in the learning process, taking a good personal approach with all school stakeholders, excellent programs (Academic Skills) that can support students to continue to work and produce achievements. develop school planning as much as possible, analyze the challenges, obstacles and future opportunities that will be faced by SMAN 2 Sidoarjo (2) the principal's strategy in improving the non-academic quality of students at SMAN 2 Sidoarjo is a superior program of life skills in the form of learning to be able to survive in life , more productive and supported by existing programs in schools. Social Skill with the hope of being able to socialize in society. Develop school planning as much as possible, analyze the challenges, obstacles and future opportunities that will be faced by SMAN 2 Sidoarjo.